Предмет: Алгебра,
автор: ghytytrg
Помогите с алгеброй пожалуйстаааа!!!!!!!!!!!!!!!!!!!!!! срочнооо
Приложения:
Ответы
Автор ответа:
0
1) ( x^( - 1 ) - 2y^( - 3 ))^2 = ( x^(-1))^2 - 2*( x^(-1))*( 2y(-3)) + ( 2y^ (- 3 ))^2 =
= x^( - 2 ) - 4x^( - 1 )y^( - 3) + 4y^( - 6 )
2) x^(-2) - 4x^(-1)y^( - 3 ) + 4y^( - 6 ) + 4x^( - 1 )y^( - 3 ) = x^( - 2 ) + 4y^( - 6 )
Ответ x^ ( - 2 ) + 4y ^ ( - 6 )
= x^( - 2 ) - 4x^( - 1 )y^( - 3) + 4y^( - 6 )
2) x^(-2) - 4x^(-1)y^( - 3 ) + 4y^( - 6 ) + 4x^( - 1 )y^( - 3 ) = x^( - 2 ) + 4y^( - 6 )
Ответ x^ ( - 2 ) + 4y ^ ( - 6 )
Автор ответа:
0
Похожие вопросы
Предмет: Английский язык,
автор: ll9234
Предмет: Литература,
автор: tatiyana333
Предмет: Информатика,
автор: dm08pvl
Предмет: История,
автор: asdf4144140